Nucleotide sequence of katG, encoding catalase HPI of Escherichia coli. - Triggs-Raine, B L (1988)
The gene katG, encoding catalase HPI of Escherichia coli, was sequenced, predicting a 726-amino-acid protein. The sequence was confirmed by identification of potential regulatory elements and amino acid sequencing of peptides. HPI shows no homology to other catalases. The distances between katG, metF, and ppc were defined.